New perspectives on Old Testament prophecy and history : essays in honour of Hans M. Barstad - Barstad, Hans M.; Thelle, Rannfrid I., 1966- (Vetus Testamentum, Supplements, 2015)
In New Perspectives on Old Testament Prophecy and History , colleagues, students, and friends of Hans M. Barstad offer essays in honour of his esteemed career in biblical studies. Contributions on prophecy include: the debate on prophets as historical figures, the biblical books of Isaiah, Ezekiel, Hosea, Amos, and Micah, and issues of methodology and interpretation. Essays devoted to history address various historiographic issues as well as specific historical topics such as the monarchy in ancient Israel, the relationship of Judah to Edom, and the ritual of reading the law. In ways that reflect Hans Barstad's innovative insights and methodological critiques, this collection of essays probes beyond the oft-trodden paths of biblical studies and challenges the status quo within the field.